Perception of Teachers and Students about Teaching and Learning in the period of Covid-19 pandemic - Silva, Osvaldo Dias Lopes da (2020)
ICERI 2020: 13th annual International Conference of Education, Research and Innovation, Sevilha, Nov 9, 2020 - Nov 11, 2020.